Implementation of a Safety Instrumented System: A Comprehensive Review and Conceptual Framework - Goeritno, Arief; Muhidin, Muhidin; Annisa, Sarah Chairul; Fitriani, Fitriani; Azama, Irham Muhammad; Waluyo, Roy; Suratun, Suratun; Muliawati, Fithri; Irawan, Joki; Ramadhan, Afham (Journal of Applied Science and Advanced Engineering, 2024)
A safety instrumented system (SIS) is specifically designed to protect personnel, pieces of equipment, and the environment by reducing the likelihood or severity of the impact of identified emergency events. This review has five objectives, i.e., (i) to find the layers of protection, (ii) to figure out and implement the SIS through life cycle step design, (iii) to find the Safety Integrity Level (SIL), (iv) to find the Safety Requirement Specification (SRS), and (v) to figure out and think about the SIS design that will be used. The study's methods are algorithms that a researcher uses to carry out research in stages of achievement and accordance with research objectives. Referring to the review proposed, five results have been achieved, which are guided by the process stages. The SIS design has been implemented and can be used as a reference for understanding the basic concepts and instrumentation of process control systems. The second is figuring out and implementing the SIS, which is an essential stage in the life-cycle step process. The third, the SIL determination, can be done using qualitative or quantitative methods that involve evaluating two risk components, e.g., probability and severity, and lies in the risk levels and the weighting structure. Furthermore, a matrix shows many of the factors that are used to determine the SIL levels. Fourth, the SRS consists of two parts, i.e., requirement specification of the functional and the integrity. Fifth, one of the considerations in designing the SIS is the separation between the SIS and the BPCS, thereby reducing the possibility of both systems failing simultaneously. Finally, the consequences range from minor injury to high death, and the main conclusion in this article is that the concept system will make it easier to find references or get predictions for determining instrumentations and creating a process control system.